Not-so-suspect terrane: Constraints on the crustal evolution of the Rudall Province - Kirkland, C.; Johnson, S.; Smithies, R.; Hollis, J.; Wingate, M.; Tyler, I.; Hickman, A.; Cliff, J.; Tessalina, Svetlana; Belousova, E.; Murphy, R. (Elsevier BV, 2013)
Time-constrained isotopic datasets permit the evaluation of tectonic processes, including continental collision, rifting, and the origins of terrane fragments. The Rudall Province, in the Paterson Orogen, is part of the West Australian Craton (WAC) and now lies to the east of the Archaean Pilbara Craton. Components within the Rudall Province have previously been linked to the Arunta Orogen of the North Australian Craton (NAC) based on similarities in timing of magmatism, deformation, and metamorphism and hence have been referred to as suspect terranes, with respect to the WAC. The Rudall Province is divided into three lithotectonic elements known as the Talbot, Connaughton, and Tabletop Terranes. The southern two terranes (Talbot and Connaughton) were affected by magmatism related to collision between the West and North Australian Cratons, during the 1800–1765 Ma Yapungku Orogeny. Zircon crystals in both Talbot and Connaughton terranes have a Hf isotopic and, in the case of inheritance, U–Pb age affinity to detritus that originated from the Capricorn Orogen basement in the WAC. Furthermore, the Hf isotopic composition of c. 1800 Ma magmatic zircons within the Rudall Province has similarity to components within the c. 1800 Ma Bridget Suite of the East Pilbara Terrane, which has an indubitable association to the Pilbara Craton. Hence, sources for all isotopic compositions preserved within the Rudall Province can be found within the proximal WAC. There is no necessity to invoke transfer of exotic NAC lithotectonic elements to the West Australian Craton margin and to suggest an accretionary style of orogenesis for the Rudall Province. The Tabletop Terrane has been regarded as a different far-travelled block with crust distinct from the other components of the Rudall Province. However, the currently available dataset implies that the Tabletop Terrane was derived from crust of similar composition to the Connaughton and Talbot terranes. A distinctive phase of crust formation at 1900 Ma is indicated by zircons, with mantle-like oxygen isotope ratios, within a c. 1450 Ma monzogranite of the Talbot Terrane. This timing of crust formation implies an affinity to a major deep lithospheric source of similar age recognized in the Musgrave Province and Edmund Basin. These data indicate that the major suture between the North and West Australian Cratons lies to the east of the Rudall Province.